Some aspects of the neuroprotective action of angiolin and cerebrocurin after prenatal alcoholization - Роpazova, O. O.; Bukhtiyarova, N. V.; Varavka, I. P.; Попазова, Олена Олександрівна; Бухтіярова, Ніна Вікторівна (Запорізький державний медичний університет, 2022)
Introduction The relevance of women's alcoholism is caused by the fact that, in the first turn, causes harm to the health of children born from this group of women.
Keywords: тези доповідей